1988
DOI: 10.1111/j.1949-8594.1988.tb11772.x
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Use of Writing in the Junior High Mathematics Classroom

Abstract: Eastern Montana CollegeBillings, Montana t . . . Writing is a mode of language that involves the active manipulation of knowledge.Î n the last five years, a call has been issued for increased student writing in the schools. One reason for this, as both Emig (1977) and Haley-James (1982) have noted, is that writing can lead to a deeper understanding and improved mastery of a topic. That is because writing is a mode of language that involves the active manipulation of knowledge. Creating an original piece of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Prior to discussing correlational results, it is important to note that the descriptive statistics presented in Tables and indicate more prevalently reported use of writing in mathematics than in prior U.S. (Bakewell, ; Pearce & Davison, ; Quinn & Wilson, ) or international (Swinson, ; Ntenza, ) samples. This suggests a possible shift in more prevalent use of such assignments and activities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to discussing correlational results, it is important to note that the descriptive statistics presented in Tables and indicate more prevalently reported use of writing in mathematics than in prior U.S. (Bakewell, ; Pearce & Davison, ; Quinn & Wilson, ) or international (Swinson, ; Ntenza, ) samples. This suggests a possible shift in more prevalent use of such assignments and activities.…”
Section: Resultsmentioning
confidence: 99%
“…Writing in Mathematics mathematics than in prior U.S. (Bakewell, 2008;Pearce & Davison, 1988;Quinn & Wilson, 1997) or international (Swinson, 1992;Ntenza, 2006) samples. This suggests a possible shift in more prevalent use of such assignments and activities.…”
Section: Itemmentioning
confidence: 98%
See 1 more Smart Citation
“…As an initial step in developing such a paradigm we surveyed 31 area junior high mathematics teachers to detennine the nature and extent of writing in their mathematics classes. Based on the analysis of these responses we classified the writing activities into five broad categories: copying, translation, journals and summaries, problem creation, and report writing (Pearce & Davison, 1988). This study found that the use of writing was sporadic and that there was almost no knowledge of writing protocols: prewriting, writing for different audiences, and revising written efforts.…”
Section: Background To Present Researchmentioning
confidence: 99%
“…Writing, especially original composition, involves the active manipulation of knowledge, many of the thought processes related to creative thinking, and the development of problem solving strategies. In short, as we have argued in Pearce and Davison, (1988) writing activities can be used to facilitate most aspects of students' mathematical development, from concept acquisition through problem solving abilities.…”
mentioning
confidence: 98%